2019
DOI: 10.2478/s11756-019-00333-9
|View full text |Cite
|
Sign up to set email alerts
|

Do wind turbines impact plant community properties in mountain region?

Abstract: The emergence of renewable energy infrastructures calls for a better understanding of their impact on biodiversity. The aim of the present study was to investigate in a mountain region the impact of a wind turbine on plant communities in their vicinity. A field survey was conducted in a wind farm situated in the Southern Romanian Carpathians, five years after the turbines were installed. We tested for the effects of the presence of the turbine and the distance to the turbine on plant species richness, on five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In situ data monitoring is one of the most accurate and reliable measurement methods, and the results of factors such as near-surface temperature, turbulence intensity, air humidity, soil temperature, wind speed, and others on the impacts of onshore wind farms on local climate indicators can be obtained by monitoring them over long time spans (Smith et al, 2013; Rajewski et al, 2014; Armstrong et al, 2016; Gao et al, 2020; Xia et al, 2022). In addition, on-site data monitoring can be used to obtain statistics on community and species changes, such as the mortality of bats, birds, and other animals, and the growth of vegetation in the local area (Barrios and Rodriguez, 2004; Arnett et al, 2008; Ma et al, 2019; Pătru-Stupariu et al, 2019; Xu et al, 2019; Liu et al, 2020; Urziceanu et al, 2021; Ferrer et al, 2022; Zhang et al, 2022). However, in situ data monitoring tools are limited by factors such as complex field conditions and monitoring time, making it more difficult to obtain long-term continuous observation data, which poses a challenge to parameterization-based studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ data monitoring is one of the most accurate and reliable measurement methods, and the results of factors such as near-surface temperature, turbulence intensity, air humidity, soil temperature, wind speed, and others on the impacts of onshore wind farms on local climate indicators can be obtained by monitoring them over long time spans (Smith et al, 2013; Rajewski et al, 2014; Armstrong et al, 2016; Gao et al, 2020; Xia et al, 2022). In addition, on-site data monitoring can be used to obtain statistics on community and species changes, such as the mortality of bats, birds, and other animals, and the growth of vegetation in the local area (Barrios and Rodriguez, 2004; Arnett et al, 2008; Ma et al, 2019; Pătru-Stupariu et al, 2019; Xu et al, 2019; Liu et al, 2020; Urziceanu et al, 2021; Ferrer et al, 2022; Zhang et al, 2022). However, in situ data monitoring tools are limited by factors such as complex field conditions and monitoring time, making it more difficult to obtain long-term continuous observation data, which poses a challenge to parameterization-based studies.…”
Section: Methodsmentioning
confidence: 99%
“…There are relatively few studies on the effects of onshore wind farms on plant communities and functions, and their conclusions vary widely. In mountainous areas, onshore wind farms have little or no effect on the five indicators of species richness and composition of plant communities, and onshore wind farms do not affect the structure of plant communities (Pătru-Stupariu et al, 2019). In desert areas, onshore wind farms significantly improve the ecosystem functioning of the whole vegetation community due to a significant influence on the local microclimate, especially on the precipitation factor, which leads to a better physiological state of the individual plants in the wind farms, with shorter and denser plants and better cover conditions (Xu et al, 2019).…”
Section: Impacts Of Onshore Wind Farms On Localized Ecologymentioning
confidence: 99%
“…For instance, Măntoiu et al (2020) demonstrated that even a minor wind energy farm of 20 wind towers could trigger high bat mortality in the absence of adequate conservation measures. To the best of our knowledge, the only study investigating the impact of wind energy towers on plant species biodiversity in Romania concluded that in the Mehedinti Mountains (SW Romania) there are no significant differences between grassland communities nearby wind towers and those situated 300 m away from towers ( Pătru-Stupariu et al, 2019 ). However, the study was performed on a small-scale wind farm and did not capture plant communities from wind tower technological platforms.…”
Section: Introductionmentioning
confidence: 99%